P34 Characterising T cell sub-populations in pulmonary hypertension. (16th November 2010) - Shepherd, AJ; Hopkinson, K; Kiely, DG; Elliot, CE; Condliffe, R; Crossman, DC; Pockley, AG; Lawrie, A
Abstract : Introduction: Pulmonary arterial hypertension (PAH) is characterised by an increase in pulmonary vascular resistance which leads to right ventricular failure and death. Given that PAH is associated with HIV (in which CD4 + lymphocytes are depleted), and that athymic rats demonstrate heightened pulmonary vascular remodelling in the SUGEN model, suggests that inflammation plays an important role in disease pathogenesis. T cells might therefore dampen rather than accentuate PAH. Hypothesis': Reduced CD4 + T cell numbers and/or an increase in the prevalence, activation and function of naturally-occurring immunoregulatory T (Treg) cells are a "second hit" in the pathogenesis of PAH′. Methodology: The T cell subset composition (CD3 +, CD4 +, CD8 + ) and prevalence of Treg cells (CD4 + CD25 bright, CD4 + CD25 bright CD127 dim, CD4 + CD25 bright CD127 dim Foxp3 +, CD4 + CD25 bright Foxp3 + ) in the peripheral blood of patients with suspected PAH attending the Pulmonary Vascular Disease Unit and corresponding controls (healthy, no PAH at right heart catheterisation with and without SSc) were determined using multi-parameter flow cytometry. The activation status (CD69 expression) of T cell subsets was also determined. Findings: Peripheral blood CD3 + T cells show heightened activation in patients with PAH compared to controls. The proportion of circulating CD4 + T cells is reduced in patients with Idiopathic PAH (IPAH), and CD4 + T cells are less activated in patients with limited and diffuse PAH associated with systemic sclerosis (PAH-SSc). The proportion of circulating CD8 + T cells is higher in patients with diffuse PAH-SSc, and CD8 + T cells are more activated in patients with IPAH than in their controls. The proportion of CD4 + CD25 high FoxP3 + Treg cells is decreased in patients with limited SSc-PAH compared to controls, and compared with controls, these cells are less activated in IPAH and limited SSc-PAH. Conclusions: These data indicate that circulating T cell subset profiles are altered in patients with PAH and a changing T cell subpopulation profile might therefore be a potential biomarker of disease or provide insight into future therapeutic targets. Studies to determine the influence of disease progression on T cell subpopulations, the functional properties of Treg cells in patients with PAH and the interaction ofthese cells with pulmonary artery endothelial cells in vitro are currently underway.